BUILDING SOCIAL PRESTIGE OF EDUCATION THROUGH LOCAL CULTURE OF BELIS FOR MANGGARAI PEOPLE - Femberianus Sunario Tanggur; Tri Marhaeni Pudji Astuti; Muh Sholeh; I G W Wisnuwardana; Saddam Saddam; Nuryanti Nuryanti (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
This research aims to explore the relationship between Belis culture and the social prestige of education for the Manggarai community. The main focus of this research is to analyze how Belis culture can influence access to and motivation for education, especially for women, as well as its impact on social dynamics in the community. This research uses a qualitative approach with a case study method. The research subjects involved three main groups: teachers, students and parents, and community leaders. Data were collected through in-depth interviews, participatory observation and focus group discussions (FGDs). The results show that the Belis culture, which is a dowry given in marriage, plays a significant role in building the social prestige of education, with highly educated women receiving greater rewards in the form of higher Belis values. On the other hand, while this culture provides incentives for women to pursue higher education, economic pressures are a major challenge for families who cannot afford the high Belis obligations, resulting in limited access to education for children, especially girls. This research suggests that the Belis culture be utilized as a driver of educational motivation, by integrating educational incentives for families committed to the quality of their children's education. In addition, to reduce social inequality, efforts to improve access to education through family economic empowerment need to be made.